A Review on Ontology - Deepika; Khurana, Dhiraj (International Journal of Computer Sciences and Engineering, 2019)
Ontology and its role in different domain like Tourism, Agriculture, Music, Recommenders, industry 4.0, and big data is mostlyused in literature. With the growing structure of W3 among artificial intelligencetechnique web 2.0 replaced with semantic web. SPARQL, DL-Querywith their flavors are widely used in industry to retrieve information from the semantic web. Reasoning among the semantics are becoming popular in ontology. In this paper our main objective is to revision the various semantic web technology using ontology.